A Comparative Study of Outcomes of Sublay Versus Onaly Mesh Repair at PMCH Nawabshah (Medical Forum Monthly, 2024)
ABSTRACTObjective: To evaluate the outcomes of the Sublay and Onlay mesh repair techniques in ventral hernias.Study Design: Prospective studyPlace and Duration of Study: This study was conducted at the Surgical Department of PMC Hospital Nawabshah from March 2016 to February 2018.Materials and Methods: This is a study of 200 patients included both gender male and female (140 female and 60 male) of incisional hernia, Paraumbilical hernia and epigastric hernia. Operative time and complications of surgical techniques like seroma formation, wound infection, mesh removal and recurrence were noted separately and compared between Sublay and Onlay mesh repair techniques.Results: Common complication observed is the seroma formation 14%, while other complications were as wound infection 10%, mesh removal 2% and recurrence 2%.Conclusion: In our study, the more beneficial surgical procedure with lesser complications patients suffering from ventral abdominal wall hernias is Sublay mesh repair.